2018
DOI: 10.4102/sajid.v33i2.17
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility of Mycoplasma genitalium isolates from Pretoria, South Africa in 2012 and 2016

Abstract: Background: Mycoplasma genitalium is a sexually transmitted pathogen associated with non-gonococcal urethritis and cervicitis. Azithromycin regimens have been considered first-line treatment for M. genitalium infections, with fluoroquinolone regimens effective as second-line treatments. However, the proportion of M. genitalium harbouring macrolide or fluoroquinolone resistance-associated mutations has been increasing worldwide. This study was done to compare the genotypic macrolide and fluoroquinolone resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…In the absence of routine diagnostics, resistance data of M. genitalium in Africa are scarce and limited to small series of asymptomatic infections in women. 9,10 The case that we report highlights a potential limitation of syndromic management in the context of macrolide-resistant M. genitalium infection. As per guidelines, our patient was treated twice with azithromycin and ceftriaxone, but without success.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the absence of routine diagnostics, resistance data of M. genitalium in Africa are scarce and limited to small series of asymptomatic infections in women. 9,10 The case that we report highlights a potential limitation of syndromic management in the context of macrolide-resistant M. genitalium infection. As per guidelines, our patient was treated twice with azithromycin and ceftriaxone, but without success.…”
Section: Discussionmentioning
confidence: 89%
“…In the absence of routine diagnostics, resistance data of M. genitalium in Africa are scarce and limited to small series of asymptomatic infections in women. 9,10…”
Section: Discussionmentioning
confidence: 99%
“…27,28,29,30 The emergence of macrolide resistance in M. genitalium has drawn recent attention. 18,20,21,22,23 The first study to report on macrolide resistance in M. genitalium in South Africa was conducted by Hay et al in the Limpopo province of rural South Africa in 2015. 20 In that study, the authors reported detecting macrolide resistance-associated mutations in 4 out of 41 (9.8%) of M. genitalium positive isolates obtained from http://www.sajid.co.za Open Access…”
Section: Discussionmentioning
confidence: 99%
“…15,16,17 In a study conducted in Pretoria, South Africa, in 2012 and 2016, the prevalence of M. genitalium in termination of pregnancy attendees was reported to be 6.0% in 2012 and 7.7% in 2016. 18 Current South African Sexually Transmitted Infections Management Guidelines (2015) recommend the administration of a single oral dose (1 g) of azithromycin for the treatment of http://www.sajid.co.za Open Access vaginal discharge syndrome and male urethritis syndrome. 19 However, recent years have seen the rapid emergence of macrolide resistance in M. genitalium as a result of this widespread administration of azithromycin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation